1986
DOI: 10.1007/bf00633191
|View full text |Cite
|
Sign up to set email alerts
|

The cardio-selectivity of himbacine: a muscarine receptor antagonist

Abstract: The antimuscarinic actions of himbacine were compared with those of atropine and/or homatropine on atria, ileum and trachea from guinea-pigs and rat uterus preparations. The antagonism of acetylcholine or carbachol by all the antagonists was competitive on the preparations studied. The pA2 values of himbacine in all smooth muscle preparations were similar (around 7.2) whereas in atria it exhibited about 10-fold higher affinity (pA2 = 8.2). In contrast, both atropine and homatropine had similar affinities for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
1

Year Published

1986
1986
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(25 citation statements)
references
References 7 publications
1
22
1
Order By: Relevance
“…The M2 subtype appears heterogeneous in both functionai and biochemical studies. In fact, cardiac muscarinic receptors differ so extensively from those of smooth muscle and exocrine glands in their properties as to suggest the existence ofdistinct subtypes (Barlow et al, 1976;Stockton et al, 1983;Mutschler & Lambrecht, 1984;Anwar-ul et al, 1986;Giachetti et al, 1986;Hammer et al, 1986). However, since our study is mainly concerned with drugs interacting with the Ml subtype, the receptors which display low affinity for pirenzepine are generically termed peripheral muscarinic subtypes in the context of this paper.…”
Section: Discussionmentioning
confidence: 93%
“…The M2 subtype appears heterogeneous in both functionai and biochemical studies. In fact, cardiac muscarinic receptors differ so extensively from those of smooth muscle and exocrine glands in their properties as to suggest the existence ofdistinct subtypes (Barlow et al, 1976;Stockton et al, 1983;Mutschler & Lambrecht, 1984;Anwar-ul et al, 1986;Giachetti et al, 1986;Hammer et al, 1986). However, since our study is mainly concerned with drugs interacting with the Ml subtype, the receptors which display low affinity for pirenzepine are generically termed peripheral muscarinic subtypes in the context of this paper.…”
Section: Discussionmentioning
confidence: 93%
“…Using autoradiographic techniques, we have shown that in a cell culture preparation of guinea-pig atria, muscarinic receptors are present on all intracardiac neurones and atrial myocytes (Hassall, Buckley & Burnstock, 1987). The receptors present on mammalian cardiac muscle have been shown to be of a predominantly M2 subtype, characterized as having a low affinity for pirenzepine and a high affinity for the antagonist 11 - [[2 -[(diethylamino)methyl] -1 -piperidinyl]acetyl] -5,11 -dihydro -6H-pyrido [2,3-b][1,4]benzodiazepine-6-one (AF-DX 116) and himbacine (Anwar- UL, Gilani & Gobbin, 1986;. However, a small percentage of the muscarinic receptors in the heart were found to be of the M1 subtype, a type commonly found within autonomic ganglia (Watson, Yamamura & Roeske, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Both these antagonists were more potent on ileum than on atrium. Only gallamine had the reverse selectivity but results obtained with this compound are difficult to interpret due to its allosteric activity (Stockton et al, 1983 (Giachetti et al, 1986), methoctramine (N,N'-bis[6-[(2-methoxybenzyl)amino]-hexyl]-1,8 -octanediamine tetrahydrochloride) (Melchiorre et al, 1987) and himbacine (Anwar-ul et al, 1986).…”
Section: Introductionmentioning
confidence: 99%